Circadian changes in estimated hepatic blood flow in healthy subjects. - Lemmer, B (1991)
Intravenous injections of indocyanine green (ICG) were given to 10 healthy supine subjects at 02.00, 08.00, 14.00 and 20.00 h. ICG plasma half-life, plasma clearance and estimated hepatic blood flow (EHBF), but not volume of distribution, varied significantly with time of day with EHBF being greatest at 08.00 h. This circadian rhythm in EHBF should be considered when evaluating the kinetics of high-clearance drugs at different times of day.